2019
DOI: 10.1159/000495581
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Epithelial Cells Promote the Differentiation of Th2 Lymphocytes in Airway Microenvironment through Jagged/Notch-1 Signaling after RSV Infection

Abstract: Background: The aim of this study was to investigate the role of Notch-1 signaling through Notch-1 ligands on bronchial epithelial cells (BECs) in regulating the development of T helper 2 (Th2) lymphocytes after RSV infection. Methods: Firstly, we analyzed the expression of cytokines and Notch-1 ligands in BECs by using real-time PCR. Then, RSV-infected BECs were co-cultured with CD4+ T cells in a transwell chamber for 48 h, and differentiation of T cells in the lower chamber was determined using fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…1, 5, and 6, they enhance the production of MCP-1, IL-6, and IL-8, resulting in the subsequent suppression of neutrophil apoptosis. Bronchial cells express various cytokines that regulate the Th1, Th2, and Th17 immune responses [21,22]. A recent study reported that S100A9 triggers the development of neutrophilic inflammation by elevation of IL-1β, IL-17 and IFN-γ, and induces allergen-induced Th2 type inflammation by production of thymic stromal lymphopoietin (TSLP) and IL-2 production [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…1, 5, and 6, they enhance the production of MCP-1, IL-6, and IL-8, resulting in the subsequent suppression of neutrophil apoptosis. Bronchial cells express various cytokines that regulate the Th1, Th2, and Th17 immune responses [21,22]. A recent study reported that S100A9 triggers the development of neutrophilic inflammation by elevation of IL-1β, IL-17 and IFN-γ, and induces allergen-induced Th2 type inflammation by production of thymic stromal lymphopoietin (TSLP) and IL-2 production [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the reduction of Jagged1 expression with siRNA abrogates this effect and promotes an increase in Th1 differentiation. On this basis, it has been suggested that Jagged1-mediated Th2 differentiation may cause RSV-induced airway hyperresponsiveness [37]. On the basis of these studies, it could be hypothesised that it may be preferable targeting specific components of the Notch signalling, such as Dll4 or Jagged1, rather than inhibiting Notch with a GSI.…”
Section: Notch and The "Cytokine Storm"mentioning
confidence: 99%
“…For hRSV, epithelial cells have been seen to contribute to the promotion of local inflammation and angiogenesis, the recruitment of various inflammatory cell types, and the development of a harmful T H 2 adaptive immune response. Many of these studies are based on in vitro models, and we only discuss the secretion of cytokines that have been observed in at least one type of human primary cell culture [ 118 , 230 , 247 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 , 298 ].…”
Section: Role Of the Respiratory Epithelium During The Immune Respmentioning
confidence: 99%
“…These cytokines greatly influence antigen-presenting cells and ILC2s, driving IL-4, IL-5, and IL-13 secretion that will ultimately lead to antibody-mediated adaptive immune responses, rather than a cytotoxic response [ 288 ]. Moreover, epithelial cells have been found to interact with CD4 + T cells via the Jagged/Notch-1 contact-dependent axis, directly influencing T H 2 differentiation in vitro [ 289 ].…”
Section: Role Of the Respiratory Epithelium During The Immune Respmentioning
confidence: 99%